An Overview of the Impact of the War of Independence and the Sir Syed Movement on Urdu Literature (Prose) - Afzal Butt, Muhammad (sourcecoder, 2022)
After the freedom war of 1857, when the Hindus and Muslims became aware politically, the question of language arose with full swing. Ali Gharrh movement of Sir Sayed which was political in nature, became the protostar of Urdu language and set a goal to make the fate of the Muslims better along with the progress and the spread of Urdu language. Therefore, the progress of Urdu under the supervision and support of Sir Sayed can never be neglected. In this movement along with Sir Sayed Ahmad Khan, Maulana Shibli Nomani added a new style in Urdu literature. It was because of Sir Sayed Ahmed Khan that nation got rid from the dilemma of religion and nationalism. The wave of awareness spread among the nation. The writers connected to the movement wrote about the Religion, politics, history and education which created a social awareness and real consciousness among the masses. The distress and disappointment of the nation last it’s breathe. Healthy and positive activities were promoted, the combination of rationalism and naturalism created such a literature which had great impact on overall literature and society.